The confrontation between Schrödinger and Heisenberg on the status of Quantum Mechanics - Simões, Eduardo (Argumentos - Revista de Filosofia, 2026)
The article analyzes the ontological confrontation between the quantum representations of Heisenberg and Schrödinger. While Heisenberg, aligned with the Copenhagen interpretation, proposes an anti-realistic, acausal and probabilistic view of microscopic reality, Schrödinger defends a realistic, continuous and visualizable interpretation of the wave function. The divergence between the two, however, goes beyond the methodological level and reveals philosophical tensions over the status of physical reality. Heisenberg rejects pictorial representation in favour of an abstract mathematical formalization. Schrödinger, on the other hand, insists on the space-time intelligibility of quantum phenomena. The clash expresses different worldviews and remains relevant in contemporary discussions about the status of quantum mechanics.